Conn's current therapy 2021 - Kellerman, Rick D. (Elsevier, 2021)
Offers personal approaches from recognized leaders in the field, covering common complaints, acute diseases, and chronic illnesses along with the most current evidence-based clinical management options. Includes new and significantly revised chapters on COVID-19, Diabetes Mellitus in Adults, Chronic Leukemias, and Osteomyelitis.